Posições de poder e influência nos fluxos de relações em uma agência de desenvolvimento regional do estado de Santa Catarina - Packer, Osni (Universidade do Vale do Rio dos Sinos, 2018)
The Government of the State of Santa Catarina implemented an administrative reform, establishing the decentralization of the government structure, with the creation of Regional Development Agencies (ADRs), whose objective is to enable the execution of several projects and actions in its region of insertion. The purpose of this study was to analyze the functioning of an ADR, based on communication flows, strategic interaction, technical approvals and / or approvals of projects, and the positions of power and influence of its actors. In order to study this new reality, the 12th ADR of Rio do Sul was selected. The methodology of social network analysis (ARS) and the quantitative approach were chosen. Several structural properties were measured at network and actor level, and sociograms were elaborated for each of the relationships established. It was concluded that the network presents a low density and little cohesion. It is rather concentrated on certain actors identified with power and influence; and there are many peripheral actors. The low connection between the actors results in a very low amount of power in the network. The actors who concentrated the greatest power and influence were the Regional Executive Secretary, followed by the Administration, Finance and Accounting Manager, the Education Manager and the Legal Adviser in the exchange of information as to the search for interaction, and in the authorizations and / or approvals of projects include the Regional Executive Secretary, the Legal Adviser and the Internal Control. Compared with the concept of ADR, it has been found that the functioning of the Agency in practice is fragile and, because it is a sparse network whose operation is concentrated in few actors, and the peripheral actors do not contribute significantly to its performance, presents difficulties mainly in the operationalization of the projects. It is suggested a restructuring that brings together the peripheral actors in all the flows or a structure with smaller number of actors for greater agility. This study provides parameters for public managers to analyze administrations focused on a new structure and governance. For the academy, the study contributed to the growth of knowledge about the field studied, from the perspective of social networks.
Keywords: Desenvolvimento regional; Descentralização; Redes; ARS; Poder e influência; Regional development; Decentralization; Networks; ARS; Power and influence; ACCNPQ::Ciências Sociais Aplicadas::Administração